A Novel Bat Coronavirus Closely Related to SARS-CoV-2 Contains Natural Insertions at the S1/S2 Cleavage Site of the Spike Protein - Zhou, Hong; Chen, Xing; Hu, Tao; Li, Juan; Song, Hao; Liu, Yanran; Wang, Peihan; Liu, Di; Yang, Jing; Holmes, Edward C.; Hughes, Alice C.; Bi, Yuhai; et al. (Current biology, 2020)
The unprecedented pandemic of pneumonia caused by a novel coronavirus, SARS-CoV-2, in China and beyond has had major public health impacts on a global scale [1, 2]. Although bats are regarded as the most likely natural hosts for SARS-CoV-2 [3], the origins of the virus remain unclear. Here, we report a novel bat-derived coronavirus, denoted RmYN02, identified from a metagenomic analysis of samples from 227 bats collected from Yunnan Province in China between May and October 2019. Notably, RmYN02 shares 93.3% nucleotide identity with SARS-CoV-2 at the scale of the complete virus genome and 97.2% identity in the 1ab gene, in which it is the closest relative of SARS-CoV-2 reported to date. In contrast, RmYN02 showed low sequence identity (61.3%) to SARS-CoV-2 in the receptor-binding domain (RBD) and might not bind to angiotensin-converting enzyme 2 (ACE2). Critically, and in a similar manner to SARS-CoV-2, RmYN02 was characterized by the insertion of multiple amino acids at the junction site of the S1 and S2 subunits of the spike (S) protein. This provides strong evidence that such insertion events can occur naturally in animal betacoronaviruses. •Metagenomic analysis identified a novel coronavirus, RmYN02, from R. malayanus•RmYN02 was the closest relative of SARS-CoV-2 in most of the virus genome•Two loop deletions in RBD may reduce the binding of RmYN02 with ACE2•RmYN02 contains an insertion at the S1/S2 cleavage site in the spike protein Zhou et al. report a bat-derived coronavirus, RmYN02, which is the closest relative of SARS-CoV-2 in most of the virus genome reported to date. RmYN02 contains an insertion at the S1/S2 cleavage site in the spike protein in a similar manner to SARS-CoV-2. This suggests that such insertion events can occur naturally in animal betacoronaviruses.